Інноваційні методики викладання технічних дисциплін - Петриченко, Сергій Володимирович; Петриченко, Сергей Владимирович; Petrychenko, Serhii; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Oleksiienko, Vadym (ТДАТУ, 2017)
UK: У роботі представлений досвід практичної реалізації досить універсальних інтерактивних форм навчання, які можуть бути органічно вбудовані в процес викладання технічних дисциплін професійного циклу. Відбиті в статті інтерактивні форми дозволяють у значній мірі активізувати учбово-пізнавальну діяльність студентів. EN: In-process the presented experience of practical realization enough universal interactive forms of studies, that can be organically built-in in a process teaching of technical disciplines of professional cycle. The interactive forms removed in the article allow in a considerable measure to activate educational-cognitive activity of students.
Innovative methodologies of teaching of technical disciplines
Keywords: ефективність навчання; інтерактивні форми навчання; активізація учбово-пізнавальної діяльності; технічні дисципліни; підвищення ефективності освітнього процесу; efficiency of studies; interactive forms of studies; activation of educational-cognitive activity; technical disciplines; increases of efficiency of educational process